Polymerization of photocurable commercial dental methacrylate-based composites - Photocalorimetry study - Gatti, A.; Rastelli, A. N. S.; Ribeiro, Sidney José Lima [UNESP]; Messaddeq, Younes [UNESP]; Bagnato, V. S. (Springer, 2007)
Due to their excellent aesthetics, photopolymers have been extensively used in several dentistry applications. However, several problems are reported, e.g. low mechanical and abrasion resistance, shrinkage during polymerization, etc. Properties of the final restorations are intrinsically related to the polymerization stage, which can be conveniently studied by photocalorimetry. In the present work the polymerization reaction and the filler content of different photocurable commercial dental methacrylate-based composites were studied by means of photocalorimetry and thermogravimetry, respectively. The results show that the values of curing rate, the heat of polymerization and the filler content vary significantly from one composite to another.
Keywords: composite resin; dental polymers; photocalorimetry; polymerization kinetics